General combining ability of parents and specific combining ability of crosses for yield and oil related traits in sunflower (Helianthus annuus L.): GCA OF PARENTS AND SCA OF CROSSES FOR YIELD AND OIL RELATED TRAITS IN SUNFLOWER - K VARALAKSHMI; S NEELIMA (Journal of Oilseeds Research, 2019)
Twenty four hybrids along with ten parents and four standard checks were evaluated in a Randomized block design with two replications at Regional Agricultural Research Station, Nandyal during rabi, 2018-19. The analysis exhibited significant differences among lines for ten traits and testers for nine traits. The lines x tester interactions were significant for eleven traits. The mean squares with respect to crosses were significant for all the characters except stem girth. The GCA and SCA variances revealed existence of non-additive gene action for most of the traits. The parental line CMS 30 A was a good general combiner as it possessed significantly high GCA effects for most of the economic traits like leaf area index, plant height, head diameter, number of leaves per plant, days to maturity, 100 seed weight, autogamy per cent, seed yield, hull content, oil content and oil yield, while NDLA-4 was a good general combiner for specific leaf area, number of leaves per plant, number of seeds per head and volume weight. The tester NGM-16 was a good general combiner for seed yield and yield component traits. The crosses NDLA-3x NO-30, CMS-30 A x R-106 and NDLA-4 x NGM-16 were promising hybrid combinations for seed yield with regard to specific combining ability (SCA) effects and these hybrids could be tested in multi location trials further if they have exploitable level of commercial heterosis .